1982
DOI: 10.1111/j.1432-1033.1982.tb06817.x
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Pig Intestinal Microvillus Maltase/Glucoamylase

Abstract: 1. Pig intestinal microvillus maltase/glucoamylase (EC 3.2.1.20) was solubilized from microvillus membranes using Triton X-I 00 and was purified by a specific anti-(maltase/glucoamylase) immunoadsorbent using elution with hypotonic solution. The specific activity was 20 -35 U x mg-' and the yield 13 %. The enzyme preparations were free of other known microvillus disaccharidases and peptidases (less than 0.4%) and showed one precipitate in crossed immunoelectrophoresis.2. The Triton-solubilized maltase/glucoamy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
1

Year Published

1983
1983
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(52 citation statements)
references
References 30 publications
4
47
1
Order By: Relevance
“…Whereas the activities of membrane-bound enzymes [aminopeptidase N (EC 3.4.11.2) and dipeptidy1 peptidase IV (EC 3.4.14.5)] could be partially recovered in the membrane fraction after the alkaline treatment (about 40%), they were totally absent in the supernatant. The exclusive presence in the membrane fraction of major bands of Mr 240000 and a blur of bands of M, 120000-150000, representing maltase-glucoamylase (EC 3.2.1.20), sucrase-isomaltase (EC 3.2.1.48-10) and aminopeptidase N [17,19,20] confirmed this finding ( fig. IA).…”
Section: Alhaline Treatment Of Microvilli Releasessupporting
confidence: 74%
See 1 more Smart Citation
“…Whereas the activities of membrane-bound enzymes [aminopeptidase N (EC 3.4.11.2) and dipeptidy1 peptidase IV (EC 3.4.14.5)] could be partially recovered in the membrane fraction after the alkaline treatment (about 40%), they were totally absent in the supernatant. The exclusive presence in the membrane fraction of major bands of Mr 240000 and a blur of bands of M, 120000-150000, representing maltase-glucoamylase (EC 3.2.1.20), sucrase-isomaltase (EC 3.2.1.48-10) and aminopeptidase N [17,19,20] confirmed this finding ( fig. IA).…”
Section: Alhaline Treatment Of Microvilli Releasessupporting
confidence: 74%
“…The membrane-bound polypeptides exhibited a different pattern. Pancreatic proteinases are known to cleave the most abundant microvillar enzymes in vivo [ 17,19,20]. Since labelling in organ culture was performed in the absence of pancreatic proteinases, the two lanes of membrane-bound polypeptides in fig.1 cannot be directly compared.…”
mentioning
confidence: 99%
“…For pig sucraseisomaltase and maltase-glucoamylase, it has been shown that the extracellular proteolytic cleavage of the precursors has little, if any, effect on the specific activity (Sjostr6m et al, 1980;S0rensen et al, 1982), but it is unknown whether the same holds for the intracellular cleavage of y-glutamyl transpeptidase and lactase-phlorizin hydrolase. The importance of high-mannose glycosylation for biological activity has generally been found to vary considerably for various proteins (Gibson et al, 1980), but the drastic effect of tunicamycin (Danielsen & Cowell, 1984) suggests that it is essential for the correct folding of at least some microvillar enzymes.…”
Section: Other Types Of Intracellular Processingmentioning
confidence: 99%
“…before the appearance of SI mRNA, is, as mentioned in section 3, unrelated to the sucraseisomaltase complex and does not indicate an early, isolated synthesis of the isomaltase subunit alone (the cDNA probe used encompassed the whole of the isomaltase portion also). This early isomaltase activity is either due to a kindred enzyme, the glucoamylase complex (which is known to appear slightly ahead of sucrase-isomaltase [33f and may have some isomaltase activity [21][22][23][24][25]), or, more probably, to a lysosomal enzyme [32].…”
Section: Methodsmentioning
confidence: 99%